Cancer screening via infrared spectral cytopathology (SCP): results for the upper respiratory and digestive tracts. Issue 2 (30th September 2015) - Diem, Max; Miljković, Miloš; Bird, Benjamin; Mazur, Antonella I.; Schubert, Jen M.; Townsend, Douglas; Laver, Nora; Almond, Max; Old, Oliver
Abstract : Instrumental advances in infrared micro-spectroscopy have made possible the observation of individual human cells and even subcellular structures. Abstract : Instrumental advances in infrared micro-spectroscopy have made possible the observation of individual human cells and even subcellular structures. The observed spectra represent a snapshot of the biochemical composition of a cell; this composition varies subtly but reproducibly with cellular effects such as progression through the cell cycle, cell maturation and differentiation, and disease. The aim of this summary is to provide a synopsis of the progress achieved in infrared spectral cytopathology (SCP) – the combination of infrared micro-spectroscopy and multivariate methods of analysis – for the detection of abnormalities in exfoliated human cells of the upper respiratory and digestive tract, namely the oral and nasopharyngeal cavities, and the esophagus.